Shipping markets in turmoil: An analysis of the Covid-19 outbreak and its implications - Michail, Nektarios A.; Melas, Kostis D. (My University, 2020)
In the current study, we examine, for the first time in the literature, the impact of exogenous effects in the shipping industry by employing data from the recent Covid-19 pandemic outbreak and explore the reactions of freight rates for dry bulk, clean, and dirty tankers. Our results, using both GARCH (1,1) and VAR specifications, suggest that such events are directly affecting the dry bulk and the dirty tanker segments. In addition, the results also suggest that second round effects, mostly via the decline in oil prices and, in some cases, third round effects via the impact from the stock market, also exist. Finally, by employing daily port calls a proxy variable for the demand for transportation services, we show that both the dry bulk and clean tankers are highly affected by the demand side of the economy, while vessels which transport crude oil do not register such a relationship.
Keywords: Covid-19; Freight rates; Shipping markets